Biosilicate scaffolds for bone regeneration: influence of introducing SrO. Issue 35 (19th April 2017) - Shuai, Cijun; Sun, Hang; Wu, Ping; Gao, Chengde; Yang, Youwen; Guo, Wang; Yang, Dafeng; Xu, Feng; Feng, Pei; Peng, Shuping
Abstract : Strontium (Sr), a bioactive element in natural bone, plays a crucial role in stimulating bone remodeling and inhibiting bone resorption. Abstract : Strontium (Sr), a bioactive element in natural bone, plays a crucial role in stimulating bone remodeling and inhibiting bone resorption. In this study, strontium oxide (SrO) was incorporated into biosilicate (Mg2 SiO4 /CaSiO3 ) scaffolds to improve the biological properties. The results revealed that SrO significantly enhanced cell adhesion, proliferation and the alkaline phosphatase (ALP) activity of the scaffolds. It could be explained that Sr 2+ can stimulate osteoblast-related gene expression (osteocalcin, type I collagen, Runx2, etc. ) and inhibit osteoclast differentiation. Moreover, the doped scaffolds could degrade continuously and form a dense apatite layer in SBF (simulated body fluid). Besides, the doped scaffolds possessed stable mechanical properties. However, excessive SrO led to a decrease in the strength of the scaffolds, which could be ascribed to the occurrence of unit cell volume expansion caused by the substitution of Sr 2+ for Ca 2+ in the CaSiO3 lattice. Our research indicated that the SrO doped biosilicate scaffolds have great potential for application in bone regeneration.